BIG BOOK TERHADAP KEMAMPUAN MENGENAL EKSPRESI EMOSI - Nindika, Dwi (Universitas Muhammadiyah Magelang, 2016)
This study aims to determine the effect on the ability to know the Big Book of emotional expression in children aged 2-3 yearsin PAUD Terpadu Fi Ahsani Taqwim Temanggung.Subjects in this study were selected using purposive sampling method, Research carried out by the design of experiment onegroup pretest posttest. The experimental group consisted of 30 research subjects, who received stimulation treatment using theBig Book. Methods of data collection is done through observation of the subject?s ability to recognize emotional expressionsangry, happy, sad, surprised. Conclusions in this research that analyzed data using a non-parametric test by using WilcoxonSigned Rank Test with SPSS For Windows Version 16.0.Conclusion of the study is the positive influence on the ability to know the Big Book of emotional expression in PAUDTerpadu Fi Ahsani Taqwim Temanggung. The new findings show that the Big Book can improve the ability to know theexpression of emotions.